A secure and imperceptible communication system for sharing co-ordinate data - Ranjeet Bidwe; Sahil Kale; Gautam Khaire; Jay Patankar; Deepak Mane; Suraj Sawant (Scientific Reports)
Abstract Military operations call for secure, imperceptible, and reliable communication systems for transmitting highly sensitive data such as geographical co-ordinates. This study proposes a novel hybrid framework combining AES-based encryption and hash-driven multi-image steganography to transmit co-ordinate data over TCP/IP networks securely. Our innovation lies in building an imperceptible, powerful yet computationally efficient and practical system for communicating sensitive location data. With the use of perceptual colour plane splicing to enhance imperceptibility against visual and statistical detection, we eliminate all traditional vulnerabilities in transmission as well as key exchange. To assess the effectiveness of the proposed framework, we evaluated the system through a practical test consisting of more than 100 experiments using images of various resolutions. The proposed model achieved a peak PSNR of 94.76 dB and an average PSNR exceeding 82 dB across all image types, ensuring imperceptibility well above the 36 dB visibility threshold. The mean square error (MSE) was consistently below 0.001, and histogram analysis confirmed visual consistency between cover and stego images. Modern steganographic attack tools (StegExpose, StegDetect) failed to detect hidden data, confirming robustness. Furthermore, the system maintained low transmission overhead (under 300 KB for 100 co-ordinates) and demonstrated resilience against passive attacks and advanced attackers targeting data leaks. Our work thus fills a critical research gap by designing a purpose-built, end-to-end secure transmission system for co-ordinate data, especially suited for real-time military scenarios requiring confidentiality, untraceability, and minimal visual and computational footprint.